Birds of Western Ecuador A Photographic Guide - Athanas, Nick (Princeton University Press, 2016)
Western Ecuador is famed for its astonishingly diverse birdlife, from colorful hummingbirds and outrageous toucans to more difficult groups like raptors, flycatchers, and ovenbirds. Here is the ultimate photographic guide to the spectacular birds of this region. Featuring nearly 1,500 stunning color photos of 946 species, this richly detailed and taxonomically sophisticated field guide will help you with even the toughest identification challenges. Species accounts, photos, and color distribution maps appear side by side, making it easier than ever to find what you are looking for, whether you are in the field or preparing for your trip.Features nearly 1,500 photos of 946 speciesIncludes facing-page species accounts, photos, and mapsProvides photos of multiple plumages for many speciesHelps you to differentiate between similar species